Impact of Credit and Liquidity Risk on Profitability: The Conventional Rural Banks in Riau Islands Province - Hesniati, Hesniati; Ellen, Ellen; Marheni, Dewi Khornida (Universitas Proklamasi 45, 2024)
The Covid-19 pandemic drastically changed the world economy, resulting in Indonesia experiencing an economic decline and deflation. The banking industry played a significant role in building the economy, so the financial services authority issued a circular letter regarding the provisions for implementing risk management for conventional rural banks and the new rules for implementing credit restructuring. This study analyzed the impact of credit and liquidity risk of conventional rural banks in the Riau Islands on profitability. Data were extracted from the financial services authority publication report of 42 conventional rural banks in Riau Islands during 2017-2021. The results of panel data analysis with the fixed effect model (FEM) showed that all risks were significantly associated with profitability (ROA), the authors found that the capital adequacy ratio had a positive significance, and the non-performing loan, liquid asset to total asset, loan to deposit ratio, and cash to deposit ratio harmed ROA. The results showed that bank risk management was needed to maintain the profitability of rural banks in Riau Islands Province.